Hydroxylamine-mediated C-C amination via an aza-hock rearrangement - Wang, Tao; Stein, Philipp; Shi, Hongwei; Hu, Chao; Rudolph, Matthias; Hashmi, A. Stephen K. (Nature Communications, 2021)
Despite the widespread use of anilines, synthetic challenges to these targets still exist. Selectivity is often an issue, when using the traditional nitration-reduction sequence or more modern approaches, including arene C-H aminations catalyzed by transition metals, photosensitizers, or electrodes. Accordingly, there is still a need for general methods to rapidly, directly access specific isomers of substituted anilines. Here, we report a simple route towards the synthesis of such motifs starting from benzyl alcohols, which are converted to anilines by the use of arylsulfonyl hydroxylamines, via an aza-Hock rearrangement. Good to excellent yields are observed. The method is applicable to various benzyl alcohol surrogates (such as ethers, esters, and halides) as well as simple alkylarenes. Functionalizations of pharmaceutically relevant structures are feasible under the reaction conditions. Over ten amination reagents can be used, which facilitates the rapid assembly of a vast set of compounds.
Gesehen am 17.12.2021